Refugee and Mixed Migration Flows Managing a Looming Humanitarian and Economic Crisis - Ghosh, Bimal (Springer International Publishing, 2018)
This book provides an insightful analysis of the looming refugee and mixed migration crisis in the context of four major, contemporary flows: two in west and east Europe, and one each in the Americas and Asia. The analysis, in each case, is followed by a judicious identification of the key issues involved and the presentation of a set of proposed policy responses to them. The discussion is then placed in a global setting and dovetailed with the recently launched United Nations initiative to adopt global compacts on refugees and migrants. The author brings to this book, the first of its kind, his vast experience of advising, and actively engaging with, many of the principal international organisations concerned with refugee and migration issues. This book will be of interest to researchers, students, NGOs, professional bodies, national ministries, international organisations and rights groups in the fields of economics, public finance, political economy, human rights and refugee law, and international relations and demography.